PENGARUH MODEL LEARNING CYCLE 5E TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA DI KELAS VIII SMPN 30 PADANG - RAHMADINA NASRI (Departemen Matematika, 2018)
Understanding of mathematical concepts is one of the cognitive abilities that must be possessed by every student in mathematics learning. But from student learning outcomes it can be seen that the understanding of mathematical concepts of students of VIII SMP 30 Padang is still low. An alternative that can be used as a solution to this problem is to implement a model Learning Cycle 5E. This study aims to determine whether there is an influence of the conceptual ability to of class VIII SMP 30 Padang through the model of Learning Cycle 5E. This type of research is quasi-experimental design with Static group design. Sampling was randomly selected and VIII 5 was selected as experimental class and class VIII 3 as control. The results showed that the understanding of mathematical concepts students' that applied the model of Learning Cycle 5E is better than students are learning to apply the conventional learning.Keywords – Learning Cycle 5E, the ability of understanding the concept, learning directly